Apheis: public health impact of PM10 in 19 European cities. Issue 10 (13th September 2004) - Medina, S; Plasencia, A; Ballester, F; Mücke, H G; Schwartz, J
Abstract : Study objective: Apheis is a public health surveillance system that aims to provide European, national, regional, and local decision makers, environmental health professionals, and the general public with up to date and easy to use information on air pollution and public health. This study presents the health impact assessment done in 19 cities of Western and Eastern European countries. Design: Apheis developed guidelines for gathering and analysing data on air pollution and the impact on public health. Apheis has analysed the acute and chronic effects of fine particles on premature mortality using the estimates developed by Aphea2 study and two American cohort studies. This health impact assessment was performed for different scenarios on the health benefits of reducing levels of particles less than 10 μm in size (PM10 ). Main results: PM10 concentrations were measured in 19 cities (range: 14–73 μg/m 3 ). The population covered in this health impact assessment includes nearly 32 million inhabitants. The age standardised mortality rates (per 100 000 people) range from 456 in Toulouse to 1127 in Bucharest. Reducing long term exposure to PM10 concentrations by 5 μg/m 3 would have "prevented" between 3300 and 7700 early deaths annually, 500 to 1000 of which are associated with short term exposure. Conclusions: Apheis shows that current levels of air pollution in urban Europe have a non-negligible impact on public health, and that preventive measures could reduce this impact, even in cities with low levels of air pollution.